A UK framework for the assessment and integration of different scientific evidence streams in chemical risk assessment - Barbara Doerr; Phil Botham; Gill Clare; David Gott; Alison Gowers; Valentina Guercio; Gunter Kuhnle; George Loizou; David P. Lovell; Neil Pearce; Lesley Rushton; Mireille Toledano; et al. (Regulatory Toxicology and Pharmacology, 2024)

Slow and ultra-rapid freezing protocols for cryopreserving roe deer (Capreolus capreolus) epididymal sperm collected at different times of year - J. Santiago-Moreno; C. Castaño; P. Bóveda; O. Mejía; R. Velázquez; L. Martínez-Fresneda; V. N. Flores-Gil; J. L Marcos-Beltrán; A. M. González-Guirado; M. C. Esteso; A. Toledano-Díaz; A. López-Sebastián (European Journal of Wildlife Research, 2021)

High versus standard doses of corticosteroids in severe COVID-19: a retrospective cohort study - Enric Monreal; Susana Sainz de la Maza; Elena Natera-Villalba; Álvaro Beltrán-Corbellini; Fernando Rodríguez-Jorge; Jose Ignacio Fernández-Velasco; Paulette Walo-Delgado; Alfonso Muriel; Javier Zamora; Araceli Alonso-Canovas; Jesús Fortún; Luis Manzano; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Efficient production of fatty acid methyl esters by a wastewater-isolated microalgae-yeast co-culture - Jessica K. Suastes-Rivas; Raúl Hernández-Altamirano; Violeta Y. Mena-Cervantes; Ruby Valdez-Ojeda; Tanit Toledano-Thompson; Luis R. Tovar-Gálvez; Silvia López-Adrián; Isaac Chairez (Environmental Science and Pollution Research, 2020)

The importance of naturally attenuated SARS‐CoV ‐2 in the fight against COVID ‐19 - Jean Armengaud; Agnès Delaunay‐Moisan; Jean‐Yves Thuret; Eelco van Anken; Diego Acosta‐Alvear; Tomás Aragón; Carolina Arias; Marc Blondel; Ineke Braakman; Jean‐François Collet; René Courcol; Antoine Danchin; et al. (Environmental Microbiology, 2020)
The current SARS‐CoV‐2 pandemic is wreaking havoc throughout the world and has rapidly become a global health emergency. A central question concerning COVID‐19 is why some individuals become sick and others not. Many have pointed already at variation in risk factors between individuals. However, the variable outcome of SARS‐CoV‐2 infections may, at least in part, be due also to differences between the viral subspecies with which individuals are infected. A more pertinent question is how we are to overcome the current pandemic. A vaccine against SARS‐CoV‐2 would offer significant relief, although vaccine developers have warned that design, testing and production of vaccines may take a year if not longer. Vaccines are based on a handful of different designs (i), but the earliest vaccines were based on the live, attenuated virus. As has been the case for other viruses during earlier pandemics, SARS‐CoV‐2 will mutate and may naturally attenuate over time (ii). What makes the current pandemic unique is that, thanks to state‐of‐the‐art nucleic acid sequencing technologies, we can follow in detail how SARS‐CoV‐2 evolves while it spreads. We argue that knowledge of naturally emerging attenuated SARS‐CoV‐2 variants across the globe should be of key interest in our fight against the pandemic.

Geographic variations in seed dispersal by ants: are plant and seed traits decisive? - R. Boulay; J. Coll-Toledano; A. J. Manzaneda; X. Cerdá (The Science of Nature, 2007)